2023
DOI: 10.3389/fpsyt.2023.1166273
|View full text |Cite
|
Sign up to set email alerts
|

Depression status and functional outcome of patients with ischemic stroke and the impact on caregivers living in Chengdu: a cross-sectional study

Abstract: ObjectivesTo investigate the associations between risk factors and depression symptoms in ischemic stroke (IS) survivors and the effect of IS survivors’ depression status and functional outcomes on caregiver burden in Chengdu, China.MethodsIn this cross-sectional study, we recruited a convenience sample of patients with IS and paired caregivers living in Chengdu from February 2022 to May 2022. Depression symptoms were assessed using the 17-item Chinese Hamilton Depression Rating Scale, the social support of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
1
0
0
Order By: Relevance
“…Similarly, another study also, it was reported that the impact of stroke and caregivers' load affect the patient and caregiver's life satisfaction (He et al, 2023). The results obtained from our study indicate that the caregiver and the patient' being informed of patient care or effective rehabilitative interventions being made is important.…”
Section: Discussionsupporting
confidence: 74%
“…Similarly, another study also, it was reported that the impact of stroke and caregivers' load affect the patient and caregiver's life satisfaction (He et al, 2023). The results obtained from our study indicate that the caregiver and the patient' being informed of patient care or effective rehabilitative interventions being made is important.…”
Section: Discussionsupporting
confidence: 74%